Predictive value of the albumin-bilirubin grade on long-term outcomes of CT-guided percutaneous microwave ablation in intrahepatic cholangiocarcinoma. (1st January 2019) - Ni, Jia-Yan; An, Chao; Zhang, Tian-Qi; Huang, Zhi-Mei; Jiang, Xiong-Ying; Huang, Jin-Hua
Abstract: Purpose: To assess the efficacy of the albumin-bilirubin (ALBI) grade on assessing long-term outcomes of computed tomography (CT)-guided percutaneous microwave ablation (CT-PMWA) in the treatment of patients with intrahepatic cholangiocarcinoma (ICC). Methods: Between April 2011 and March 2018, 78 patients who underwent CT-PMWA were enrolled in this study. Overall survival (OS) and recurrence-free survival (RFS) were compared in the groups stratified by the ALBI grade and Child–Pugh score. Cox proportional hazard regression analyses were performed to determine independent predictors of OS and RFS. Results: After a median follow-up of 22.7 months (range 1–86.7 months), 67 patients had died. The cumulative 1-, 3-, and 5-year OS rates were 89.5%, 52.2%, and 35.0%, respectively. Stratified by the ALBI grade, the cumulative 1-, 3-, and 5-year OS rates were 100%, 69.2%, and 25.6% for patients with the grade 1, respectively. For patients with the ALBI grade 2, the cumulative 1-, 3-, and 5-year OS rates were 41.0%, 10.3%, and 10.3%, respectively. Patients with a hepatic function of the ALBI grade 1 had significantly higher OS rates than patients with the ALBI grade 2 ( p  < .001). The multivariate analysis showed tumor size (Hazard Ratio[HR] 95% Confidence Interval[CI]:9.03[1.01–80.52], p  = .049) and the ALBI grade (HR[95%CI]:9.56[1.58–58.00], p  = .014) were associated with OS, and tumor size (HR: 2.03[0.69–8.04], p  = .049) was associated with RFS. Conclusions: The preliminary data of this study showed the ALBI grade was effective to predict long-term outcomes of CT-PMWA in ICCs. Further study is necessary to validate our results by a large, multi-center patient cohort.